Anabolic steroid usage in athletics: Facts, fiction, and public relations - Berning, J. M.; Adams, K. J.; Stamford, B. A. (The Journal of Strength and Conditioning Research, 2004)
Anecdotal evidence suggests the widespread usage of anabolic steroids among athletes (20-90%), particularly at the professional and elite amateur levels. In contrast, scientific studies indicate that usage is rare and no higher than 6%. Conclusions from scientific studies suggest that anabolic steroid usage declines progressively from high school to college and beyond; however, anecdotal evidence claims the opposite trend. In this clash between "hard" scientific data vs. "soft" anecdotal information, it is natural that professionals would gravitate toward scientifically based conclusions. However, in the case of anabolic steroids (a stigmatized and illegal substance), should word-of-mouth testimony from individuals closest to the issues—those who have participated in and coached sports, those who have served as drug-testing overseers, and journalists who relentlessly track leads and verify sources—be set aside as irrelevant? Not if a complete picture is to emerge. In this review, hard scientific evidence is placed on the table side-by-side with soft anecdotal evidence, without weighting or bias. The purpose is to allow the opportunity for each to illuminate the other and, in so doing, potentially bring us a step closer to determining the true extent of anabolic steroid usage in athletics.